Preparation and characterizations of superparamagnetic iron oxide‐embedded poly(2‐hydroxyethyl methacrylate) nanocarriers. Issue 18 (17th April 2014) - Gupta, Meher Kanta; Bajpai, Jaya; Bajpai, Anil Kumar
ABSTRACT: The present study aims at formulating a novel multifunctional biocompatible superparamagnetic nanoparticles carrier system with homogeneously dispersed magnetic material in solid polymer matrix of poly(2‐hydroxyethyl methacrylate) (PHEMA). The nanocomposites were designed by modified suspension polymerization of 2‐hydroxyethyl methacrylate followed by in situ coprecipitation of iron oxide inside the nanoparticle matrix yielding magnetic PHEMA (mPHEMA) nanocomposites. The so prepared nanocomposites were characterized by Fourier transform Infrared spectroscopy, X‐ray diffraction technique, Raman spectroscopy, electron diffraction, and energy‐dispersive X‐ray spectroscopy confirming the presence of Fe3 O4 inside the PHEMA nanoparticles. The magnetization studies of nanocomposites conducted at room temperature using vibrating sample magnetometer suggested for their superparamagnetic nature having saturation magnetization (Ms) of 20 emu/g at applied magnetic field of 5 kOe. Transmission electron microscopy, field‐emission scanning electron microscopy, and dynamic light scattering/zeta potential measurements were also performed which revealed that size of mPHEMA nanocomposites was lying in the range of 60–300 nm having zeta potential of −93 mV. The nanocomposites showed no toxicity as revealed by cytotoxicity test performed on L‐929 fibroblast by extract method. The results indicated that the prepared superparamagnetic mPHEMA nanocomposites have enormous potential to provide a possible option for magnetically assisted targeted delivery of anticancer drugs. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2014, 131, 40791. Abstract :